2022
DOI: 10.1155/2022/8074837
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Overweight among Adults in the Middle East Countries from 2000 to 2020: A Systematic Review and Meta-Analysis

Abstract: Background. Obesity has become a significant public health issue worldwide, and it is a major risk factor for many noncommunicable diseases. This systematic review aimed to identify the prevalence of obesity and overweight in the Middle East region and different countries in this region. Materials and Methods. PubMed, Google Scholar, and MEDLINE databases were searched from 2000–2020 to identify relevant studies in the Middle East area. The survey was carried out using combinations of Medical Subject Headings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 101 publications
(25 reference statements)
4
69
1
2
Order By: Relevance
“…The BMI results of African countries showed that a fairly large percentage of students were overweight and obese -31.15% and 14.75%, respectively, which was confirmed by Okati-Aliabad et al [40] who found the range of prevalence of obesity was between (15.09-30.20%) and the range of prevalence of overweight was between (28.94-32.63%).…”
Section: Discussionmentioning
confidence: 58%
“…The BMI results of African countries showed that a fairly large percentage of students were overweight and obese -31.15% and 14.75%, respectively, which was confirmed by Okati-Aliabad et al [40] who found the range of prevalence of obesity was between (15.09-30.20%) and the range of prevalence of overweight was between (28.94-32.63%).…”
Section: Discussionmentioning
confidence: 58%
“…Socio-demographic characteristics of both groups obese and control groups (non-obese) (21), where the highest age group was in Obese group years old, and also normal weight was (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) the highest percentage of participants in these study.…”
Section: Resultsmentioning
confidence: 68%
“…while, in the obese group of females was higher than males. the explanation of this result is due to the prevalence of obesity among females (28.8%) in Iraq is higher than that of males(18.0) (22).…”
Section: Resultsmentioning
confidence: 93%
“…Another study in China with 441 thousand adults reported that people aged 45–54 years had the highest frequency of overweight and obesity ( 23 ). A meta-analysis with 101 studies including 698,905 participants identified that the prevalence of obesity increased with age, and people aged > 40 years had the highest percentage of obesity and overweight in Middle East countries ( 24 ). The lower mean age in our study may account for our lower prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%